2021
DOI: 10.1016/j.jcct.2020.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vessel wall segmentation on volumetric and radiomic parameters of coronary plaques with adverse characteristics

Abstract: Background: Quantitative coronary plaque parameters are increasingly being utilized as surrogate endpoints of pharmaceutical trials. However, little is known whether differences in segmentation significantly alter parameter values. Methods: Overall, 100 coronary plaques with adverse imaging characteristics were segmented automatically, by two experts (R 1-R 2) and three nonexperts (R 3-R 5). Low attenuation noncalcified (LANCP), noncalcified and calcified plaque volume were calculated and 4310 radiomic feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 36 publications
0
14
0
2
Order By: Relevance
“…In angiography, the GLCM method is much less frequently applied, and so far, only a handful of studies have been published on this topic. These mainly include the use of GLCM features for assessment of low attenuation noncalcified (LANCP), noncalcified and calcified coronary plaques (Kolossvary et al, 2019;Kolossvary et al, 2021), or for computer-aided diagnosis-specific cases of endovascular aortic aneurysms (Garcia et al, 2014). In optical coherence tomography angiography, as demonstrated earlier, some GLCM indicators can also be applied to quantify choriocapillaris in healthy and diseased eyes (Khan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In angiography, the GLCM method is much less frequently applied, and so far, only a handful of studies have been published on this topic. These mainly include the use of GLCM features for assessment of low attenuation noncalcified (LANCP), noncalcified and calcified coronary plaques (Kolossvary et al, 2019;Kolossvary et al, 2021), or for computer-aided diagnosis-specific cases of endovascular aortic aneurysms (Garcia et al, 2014). In optical coherence tomography angiography, as demonstrated earlier, some GLCM indicators can also be applied to quantify choriocapillaris in healthy and diseased eyes (Khan et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The technique uses second-order statistics to determine indicators that reflect image features such as textural homogeneity, uniformity, and level of disorder. Previously, some of these indicators, such as angular second moment and inverse difference moment, have proven to be sensitive in assessing data obtained as the result of various X-ray digital image transformations (Chen et al, 2021;Kolossvary et al, 2021;Shankar et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Controversial results can be found in the literature concerning the reproducibility of fully automated plaque quantification methods. The study of Kolossvary et al [40] found that the automated segmentation method compared with expert readers had poor agreement regarding different quantitative plaque features with the exception of calcified plaques. On the contrary, an IVUS validated dedicated automated quantitative software analysis performed with excellent reproducibility in determining quantitative plaque parameters with intraclass correlation coefficient (ICC) of 0.880 for PB [41].…”
Section: Automated Plaque Quantificationmentioning
confidence: 99%